The usage of peer mentors in learning islamic banking: a case study at UiTM Kelantan / Zanirah Mustafa @ Busu ...[et al.]. - Mustafa @ Busu, Zanirah; Zainal, Noor Saliza; Awang Ab. Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Mat Jusoh, Nor Amira (Global Academic Excellence, 2018)
There are a variety of approach in teaching and learning at the higher learning institutions. Nowadays, students should be introduced with a method that suit their interest and need. Mentoring approach is one of the popular methods used by the lecturers and teachers. Mentoring approach is defined as a teaching method which involves a transfer of wisdom, where the mentor or coach provides advice or direction, probably based on their experience and expertise. Meanwhile in this study, the mentoring approach is tested on one group of diploma students at Universiti Teknologi MARA (UiTM), Kelantan. They were students who undertake the course of Fundamentals of Islamic Banking (CTU351) at the university. A senior student was appointed as the peer mentor by the Head of Academy of Contemporary Islamic Studies (ACIS). The peer mentor and mentees had regularly met and discussed matters pertaining to the course and studies. There are four objectives of this study, namely to determine the trend of study hour, to determine whether the students have mentor or not, to determine the difference in mean perception on mentoring approach in learning Fundamentals of Islamic Banking across selected students’ profiles and finally to identify the factors affecting the learning of Fundamentals of Islamic Banking. The results of the study show that almost half of the students studied 4 hours or more. However, more than 60% of them do not have Mentor during their studies. Moreover, the results also showed that perception on mentoring approach in learning Fundamentals of Islamic Banking does not significantly differ across students’ gender, accommodation and mentor and there is a positive effect of Classroom, outside classroom and Surroundings in the learning of Fundamentals of Islamic Banking.